Effect of Bamboo Substrate on Growth and Production of Carp and Small Indigenous Fish - Poudel, Rajan; Rai, Sunila; Jha, Dilip K; Mandal, Ram Bhajan (Our Nature, 2020)
A field trial was conducted to examine effects of substrates on yield of carp and SIS at Sukranagar Village, Chitwan district for 210 days in farmer’s pond. The experiment was designed with four treatments: T1 (carp only), T2 (carp+SIS), T3 (carp+substrate) and T4 (carp+SIS+substrate) with four replicates. Ponds were stocked with fingerlings of six carp species at a rate of 20,000 fish/ha and two Small indigenous fish species at a rate of 50,000 fish/ha in 1:1 ratio. Prior to stocking of fish, split bamboo mats were fixed in substrate ponds covering 2% of pond surface area to enhance periphyton growth. Carp were fed with dough of rice bran and mustard oil cake (1:1) at the rate of 3% BW daily while Grass carp was fed with grass and banana leaves at 50% BW. Growth and yield of Rohu and Common carp, combined net fish yield and gross margin were found higher (p<0.05) in carp ponds with substrate.